2003
DOI: 10.1046/j.1365-3156.2003.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and social risk factors for Aedes infestation in rural Thailand

Abstract: SummaryAn intense epidemic of dengue haemorrhagic fever in 1998 prompted the Thai government to investigate the feasibility of focalized vector (Aedes aegypti) control programmes. We tested for correlations of three indices of Aedes larval abundance (housing index, container index and Breteau index) against 38 socio-economic and four climatic variables. Availability of public water wells, existence of transport services and proportion of tin houses were positively associated with larval indices. Private water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 20 publications
4
82
0
5
Order By: Relevance
“…For example, the strong association between weather variables and dengue found in Barbados at a lags of 6 to 16 weeks for vapor pressure and minimum and maximum temperature, 58 the highest correlation with total rainfall a lag of seven weeks in Taiwan, 59 and the strong positive association with absolute humidity in Thailand. 33 Dengue incidence is sensitive to both periodic fluctuations and sustained changes in global and local climates, because vector biology and viral replication are dependent on temperature and moisture. 3 Nonetheless, the already published associations between dengue incidence and weather variables were more or less strong, depending in the approach of analysis and the study areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the strong association between weather variables and dengue found in Barbados at a lags of 6 to 16 weeks for vapor pressure and minimum and maximum temperature, 58 the highest correlation with total rainfall a lag of seven weeks in Taiwan, 59 and the strong positive association with absolute humidity in Thailand. 33 Dengue incidence is sensitive to both periodic fluctuations and sustained changes in global and local climates, because vector biology and viral replication are dependent on temperature and moisture. 3 Nonetheless, the already published associations between dengue incidence and weather variables were more or less strong, depending in the approach of analysis and the study areas.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,12,14 Less is known about the relation with cultural and social factors (social backwardness, the lack of water access and the use of uncovered water tanks not using mosquitoes nets, the lack of health services and health education), which also play an important role in the prevalence of the disease. 9,33,34 Also unplanned urbanization and inadequate resources for vector control are factors that promote transmission and are characteristic of poor countries. In México, Hurtado and colleagues found 14 that these dengue control activities increased only after a rise in dengue cases.…”
Section: Salud Pública De México / Vol 59 No 1 Enero-febrero De 2017mentioning
confidence: 99%
“…aegypti adult and immature abundance. 49,50 Air temperature also influences dengue virus replication in the mosquito, 15 with shorter extrinsic incubation periods at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This study enrolled 89 weather stations on the Indochina peninsula, which consistently reported all these variables between 1995 and 2004. These climatic variables were interpolated to the geographic centre (centroid) of each district, as reported previously [15].…”
Section: Climatic Datamentioning
confidence: 99%
“…Over 250 socioeconomic variables have been surveyed from each of the 61 000 Thai villages on a bi-annual basis, as described previously [15]. Data were collected in even-numbered years between 1994 and 1998 and in odd-numbered years since 2001.…”
Section: Socioeconomic Datamentioning
confidence: 99%